Denazification in Germany: basic approaches to the study of the problem in British and American historiography - Kaviaka, Iryna I. (Journal of the Belarusian State University. International Relations, 2019)
The article is devoted to the examination of the main approaches to the study of denazification policy in Germany that emerged in British and American historiography. Based on the analysis of a wide range of sources, the author established the basic concepts that were used while analyzing the goals, methods and results of denazification. The evolution of scientific assessment during the second half of the 20th – early 21st centuries contributed to revealing of the three main approaches to the study of the issue: critical, revolutionary and rationalistic. The study results and the article conclusions can be used for further research of the historical science in the UK and US, as well as certain aspects of the German problem after World War II.
Keywords: British historiography; American historiography; the German question; denazification; renazification; artificial revolution; conservative restoration; re-education